Entrepreneurial assistance across the ocean : an examination of the effectiveness of international mentoring as a support service for entrepreneurs in Samoa : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Purcell, Gisela (Massey University, 2013)
Indigenous entrepreneurs play an important role in the economic growth of developing countries but to be sustainable they must balance their business needs with the cultural norms of the local context. Donor countries are increasingly supporting the private sector through business mentoring, however the challenges facing indigenous entrepreneurs are quite different to those experienced by their mentors. This research investigates the value of donor-funded, cross-cultural mentoring through an examination of the Pacific Business Mentoring Programme, a New Zealand initiative in Samoa. Based on an extensive literature review, this thesis develops a framework to assess the value of a mentoring programme. Semi-structured interviews with 23 entrepreneurs in Samoa reveal their positive and negative experiences with the programme. An online survey of the New Zealand mentors who had worked in Samoa provides further data regarding the perceived strengths and weaknesses of the programme. This information is evaluated against the mentoring framework to assess what worked well and what areas could be improved. Research findings show that mentoring can provide both business and socio-cultural development outcomes, however economic improvements can be very difficult to attribute directly to a mentoring programme. Several cited benefits of the mentoring programme, such as providing a neutral sounding board and challenging the entrepreneur’s assumptions, are difficult to quantify. The majority of entrepreneurs believe that their mentor did not have a good understanding of the local cultural context. Where a mentor’s advice conflicted with their cultural practices, the entrepreneur would usually ignore or adapt the advice to reach a compromise. Some cultural practices appear to be detrimental to running a business, however many of these practices add to the resilience of local people as well as having a social function, and should therefore not be undermined. This thesis concludes that donor-funded business mentoring is a versatile, effective tool for development assistance if mentors are sensitive to the unique challenges of the local context and do not underestimate the abilities of the local entrepreneurs. With careful selection, training and support, mentoring can support indigenous entrepreneurs to improve their business skills while retaining their cultural identity.
Keywords: Mentoring in business; Businesspeople; Attitudes; Samoa